Skip to main content
K12 LibreTexts

3.4.3: Simplifying Trigonometric Expressions with Double-Angle Identities

  • Page ID
  • \( \newcommand{\vecs}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} } \) \( \newcommand{\vecd}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash {#1}}} \)\(\newcommand{\id}{\mathrm{id}}\) \( \newcommand{\Span}{\mathrm{span}}\) \( \newcommand{\kernel}{\mathrm{null}\,}\) \( \newcommand{\range}{\mathrm{range}\,}\) \( \newcommand{\RealPart}{\mathrm{Re}}\) \( \newcommand{\ImaginaryPart}{\mathrm{Im}}\) \( \newcommand{\Argument}{\mathrm{Arg}}\) \( \newcommand{\norm}[1]{\| #1 \|}\) \( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\) \( \newcommand{\Span}{\mathrm{span}}\) \(\newcommand{\id}{\mathrm{id}}\) \( \newcommand{\Span}{\mathrm{span}}\) \( \newcommand{\kernel}{\mathrm{null}\,}\) \( \newcommand{\range}{\mathrm{range}\,}\) \( \newcommand{\RealPart}{\mathrm{Re}}\) \( \newcommand{\ImaginaryPart}{\mathrm{Im}}\) \( \newcommand{\Argument}{\mathrm{Arg}}\) \( \newcommand{\norm}[1]{\| #1 \|}\) \( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\) \( \newcommand{\Span}{\mathrm{span}}\)\(\newcommand{\AA}{\unicode[.8,0]{x212B}}\)

    Simplify sine, cosine, and tangent of angles multiplied or divided by 2.

    As Agent Trigonometry, you are given the following cryptic clue. How could you simplify this clue?

    \(\dfrac{\tan 2x}{\dfrac{\tan x}{1+\tan x}}\)

    Simplifying Trigonometric Expressions

    We can also use the double-angle and half-angle formulas to simplify trigonometric expressions.

    Let's simplify \(\dfrac{\cos 2x}{\sin x\cos x}\).

    Use \(\cos 2a=\cos ^2a−\sin ^2a\) and then factor.

    \(\begin{aligned} \dfrac{\cos 2x}{\sin x\cos x}&=\dfrac{\cos ^2x−\sin ^2x}{\sin x+\cos x} \\&=\dfrac{(\cos x−\sin x)\cancel{(\cos x+\sin x)}}{\cancel{\sin x+\cos x }}\\&=\cos x−\sin x \end{aligned}\)

    Now, let's find the formula for \(\sin 3x\).

    You will need to use the sum formula and the double-angle formula. \sin 3x=\sin (2x+x)

    \(\begin{aligned} \sin 3x&=\sin (2x+x) \\&=\sin 2x\cos x+\cos 2x\sin x \\&=2\sin x\cos x\cos x+\sin x(2\cos ^2x−1) \\ &=2\sin x\cos ^2x+2\sin x\cos ^2x−\sin x \\&=4\sin x\cos ^2x−\sin x \\&=\sin x(4\cos ^2x−1) \end{aligned}\)

    Finally, let's verify the identity \(\cos x+2\sin ^2 \dfrac{x}{2}=1\).

    Simplify the left-hand side use the half-angle formula.

    \(\begin{aligned} &\cos x+2\sin ^2\dfrac{x}{2} \\ &\cos x+2\left(\sqrt{\dfrac{1−\cos x}{2}}\right)^2 \\ &\cos x+2\cdot \dfrac{1−\cos x}{2} \\ &\cos x+1−\cos x \\ &1 \end{aligned}\)

    Example \(\PageIndex{1}\)

    Earlier, you were asked to simplify \(\dfrac{\tan 2x}{\dfrac{\tan x}{1+\tan x}}\).


    Use \(\tan 2a=\dfrac{2\tan a}{1−\tan ^2a}\) and then factor.

    \(\begin{aligned}\dfrac{\tan 2x}{\dfrac{\tan x}{1+\tan x}}&=\dfrac{2\tan x}{1−\tan ^2x}\cdot \dfrac{1+\tan x}{\tan x} \\&=\dfrac{2\tan x}{(1+\tan x)(1−\tan x)}\cdot \dfrac{1+\tan x}{\tan x}=\dfrac{2}{1−\tan x}\end{aligned}\)

    Example \(\PageIndex{2}\)

    Simplify \(\dfrac{\sin 2x}{\sin x}\).


    \(\dfrac{\sin 2x}{\sin x}=\dfrac{2\sin x\cos x}{\sin x}=2\cos x\)

    Example \(\PageIndex{3}\)

    Verify \(\cos x+2\cos ^2 \dfrac{x}{2}=1+2\cos x\).


    \(\begin{aligned} \cos x+2\cos ^2\dfrac{x}{2}&=1+2\cos x \\ \cos x+2 \sqrt{\dfrac{1+\cos x}{2}}&= \\ \cos x+1+\cos x&= \\ 1+2\cos x&= \end{aligned}\)


    Simplify the following expressions.

    1. \(\sqrt{2+2\cos x} \left(\cos \dfrac{x}{2}\right)\)
    2. \(\dfrac{\cos 2x}{\cos ^2x}\)
    3. \(\tan 2x(1+\tan x)\)
    4. \(\cos 2x−3\sin ^2x\)
    5. \(\dfrac{1+\cos 2x}{\cot x}\)
    6. \((1+\cos x)^2 \tan \dfrac{x}{2}\)

    Verify the following identities.

    1. \(\cot \dfrac{x}{2}=\dfrac{\sin x}{1−\cos x}\)
    2. \(\dfrac{\sin x}{1+\cos x}=\dfrac{1−\cos x}{\sin x}\)
    3. \(\dfrac{\sin 2x}{1+\cos 2x}=\tan x\)
    4. \((\sin x+\cos x)^2=1+\sin 2x\)
    5. \(\sin x\tan \dfrac{x}{2}+2\cos x=2\cos ^2 \dfrac{x}{2}\)
    6. \(\cot x+\tan x=2\csc 2x\)
    7. \(\cos 3x=4\cos ^3x−3\cos x\)
    8. \(\cos 3x=\cos ^3x−3\sin ^2x\cos x\)
    9. \(\sin 2x−\tan x=\tan x\cos 2x\)
    10. \(\cos ^4x−\sin ^4x=\cos 2x\)

    Answers for Review Problems

    To see the Review answers, open this PDF file and look for section 14.16.

    This page titled 3.4.3: Simplifying Trigonometric Expressions with Double-Angle Identities is shared under a CK-12 license and was authored, remixed, and/or curated by CK-12 Foundation via source content that was edited to the style and standards of the LibreTexts platform; a detailed edit history is available upon request.

    CK-12 Foundation
    CK-12 Foundation is licensed under CK-12 Curriculum Materials License
    • Was this article helpful?